Przestępstwa skarbowe związane z uchylaniem się od opodatkowania - Karol Szymon Orzeszak (Studia i Materiały)
Fiscal crimes (tax crimes) penalized in the Fiscal Penal Code constitute a specific area of criminal law, as they lie at the junction between criminal law and tax law. Criminal fiscal law plays a key role in protecting the tax interest of a public-law entity, and more broadly, the financial interest of the state. The article comments on the crimes of tax evasion and fraud, doing business under another’s company and presents statistical data on them.